Forms And Mechanisms Of Business Dispute Resolution In Indonesia - Siahaan, Herikson P (Inspiring Law Journal, 2024)
In Indonesia, there are two types of non-litigation settlement, namely arbitration and alternative dispute resolution in accordance with UUAAPS. Alternative dispute resolution or ADR is a form of dispute resolution outside the court based on an agreement (consensus) carried out by the disputing parties either without or with the assistance of a neutral third party. Settlement of business disputes containing criminal elements through a restorative justice approach is used if there is sufficient evidence to prosecute the perpetrator of the crime and is accompanied by the freedom and voluntariness of the victim and perpetrator. Settlement is carried out as much as possible for the recovery of the victim, and is carried out if the perpetrator realizes and admits his mistake and the consequences for the victim and the community, and the perpetrator is willing to take responsibility voluntarily. By involving the community who can act as organizers, observers or facilitators